A Possible Case of Hypopituitarism in Neolithic China. (15th September 2011) - Hernandez, M.
ABSTRACT A human skeleton with a possible case of hypopituitarism is reported. The individual (burial M53) is from the site of Guanjia, a Neolithic settlement in northern China, dated to the Late Yangshao period (6000–5500 bp). On the basis of the fully erupted third permanent molars and moderate occlusal dental wear resulting in substantial exposure of dentine, the initially estimated age‐at‐death was placed between 26 and 33 years. However, dimensions of the postcranial skeleton fall significantly below and outside the range from contemporaneous adult populations, and along with delayed epiphyseal fusion present throughout the skeleton, the postcranial age is concordant to that of an 11‐ to 13‐year‐old child. Most long bone epiphyses display incomplete fusion or are entirely unfused, but a lack of microporosity in the metaphyseal areas near growth plates indicates a cessation of longitudinal bone growth. Because no signs of porotic hyperostosis, cribra orbitalia, periosteal lesions or linear enamel hypoplasia are observed, the restricted growth of this individual is likely caused by a growth hormone disorder and is unrelated to nutritional deficiencies or systemic infection. Copyright © 2011 John Wiley & Sons, Ltd.